Costing methods for combined heat-and-power plants fueled by zero-marginal cost energy sources. (1st May 2019) - Van Erdeweghe, Sarah; Van Bael, Johan; D'haeseleer, William
Highlights: Levelized cost metrics and costing methods for combined heat-and-power plants. (Near) zero-marginal cost renewable energy sources are considered. Concepts levelized cost of exergy & net present value based on exergy are proposed. Novel concepts account for two products and temperature levels (usefulness of heat). Application to a low-temperature geothermal combined heat-and-power plant. Abstract: In this paper, several cost metrics for application to a combined heat-and-power plant fueled by a zero-marginal cost energy source are studied. The mature levelized cost concepts are extended with some novel metrics such as the levelized cost of exergy . The results are given for a geothermal combined heat-and-power plant, connected to two different types of district heating systems and for two scenarios for the heat and electricity prices (high and low). For a low price scenario, the conventional costing method based on two separate prices for electrical and thermal energy is the most appropriate. Also for a high price scenario, the conventional costing method is the most appropriate for heat demands at low temperature. However, for higher-temperature heat demands, the exergy costing method results in the highest revenues for the combined heat-and-power plant. The authors recommend the use of the novel levelized cost of exergy metric as different types of energy are priced with a single value. Depending on the amount of energy and the usefulness of the energy type, an appropriate cost can be allocated to each product of a multi-energy system.